Estratégia empresarial e eficiência na concessão de crédito: o relacionamento entre a provisão para crédito de liquidação duvidosa e o desempenho no mercado financeiro - Scavone, Tiago Mendonça (2018)
The purpose of this dissertation was to analyze whether there is a correlation between the variation in the Loan Loss Provisions, the Kanitz Thermometer and the Financial Performance of the Ordinary Shares (ON) of Banco do Brasil S/A. The theoretical basis was provided by three main constructs. The first deals with Business Strategy from the studies of Drucker (1994), Porter (1996) and Mintzberg et al (2010), with RBT (Resource-Based Theory), through the VRIO model of Barney and Hesterly (2011). The second is related to the economic management according to Brito et al (2005) and Assaf Neto (2015) and analysis of the Financial Indicators according to Iudícibus (1988), Carvalho et al (2017), Franco (2006), Marion (2009) and Ribeiro et al (2013). The third construct addresses the Kanitz Thermometer (Kanitz, 1978), the importance of the company's solvency and insolvency margin according to Silva and Carvalho (2015), highlighting its ability to meet its obligations, as stated by Matarazzo (2013) and Melo e Coutinho (2005). The Kanitz Thermometer was designed to analyze the financial health of a company and to verify if there is any risk of bankruptcy in the near future (Kassai, 2000; Gomes et al, 2015). The objective of this research is to analyze if there is a connection between the variation (increase or decrease) of the Allowance For Doubtful Accounts in the financial performance of the ON shares traded in B3 during the period from 2006 to 2016. The theoretical justification is to increase the number of works related to the topic. The research methodology was quantitative with the analysis of secondary data collected in accounting with the Economática software. The samples investigated were 44 trimesters and the statistical analysis used was correlation or Pearson’s r. Of the proposed hypotheses only the third was confirmed with a negative and moderate correlation and with a significance of 0.00%. In this way it is possible to conclude that investors did not take into account the variation of the Loan Loss Provisions or the index in the Kanitz Thermometer when they made their investments in the subsequent trimester. Suggestions for future research are to expand the number of financial institutions with shares traded on B3 and expand the parameters of financial performance such as ROE, ROA and Stress Testing.